Exposure to cobalt chromium dust and lung disorders in dental technicians. Issue 7 (July 1995) - Seldén, A I; Persson, B; Bornberger-Dankvardt, S I; Winström, L E; Bodin, L S
Abstract : BACKGROUND–Dental technician's pneumoconiosis is a dust-induced fibrotic lung disease of fairly recent origin. This study was carried out to estimate its occurrence in Sweden. METHODS–Thirty seven dental technicians in central and south eastern Sweden with at least five years of exposure to dust from cobalt chromium molybdenum (CoCrMo) alloys, identified by postal survey, agreed to undergo chest radiography and assessment of lung function and exposure to inorganic dust. RESULTS–Six subjects (16%; 95% confidence interval 6% to 23%) showed radiological evidence of dental technician's pneumoconiosis. The lung function of the study group was reduced compared with historical reference material. With local exhaust ventilation dust levels were generally low, whereas in dental laboratories without such equipment high levels of dust, particularly cobalt, were found. CONCLUSIONS–Pneumoconiosis may result from exposure to inorganic dust in the manufacturing of CoCrMo-based dental constructions. It is possible to reduce this hazard substantially by local exhaust ventilation.